Zinc oxide nanosphere for hydrogen sulfide scavenging and ferroptosis of colorectal cancer - Xiang Pan; Yuchen Qi; Zhen Du; Jian He; Sheng Yao; Wei Lu; Kefeng Ding; Min Zhou (2021)
Colorectal cancer is a common malignancy occurring in the digestive system and ranks second in cancer mortality worldwide. In colorectal cancer, hydrogen sulfide (H2S) is selectively upregulated, resulting in the further exacerbation of the disease. Therefore, the clearance of H2S and the regulation of the enzymes on the H2S pathways are of great significance for colorectal cancer therapy.Here, we investigated the H2S content in various clinical tumor tissues from patients and confirmed that overproduced concentration of H2S in colorectal cancer. Accordingly, we developed an H2S-responsive nanoplatform based on zinc oxide coated virus-like silica nanoparticles (VZnO) for the therapy of colorectal cancer.Owing to its excellent H2S scavenging ability, VZnO could effectively reduce H2S content in colorectal cancer to prohibit the growth of CT26 and HCT116 colorectal cancer cells. Moreover, the removal of H2S in colorectal cancer also leads to tumor inhibition through activating ferroptosis, a non-apoptotic form of cell death. The biosafety-related toxicological and pathological analysis confirmed the low toxicity and high safety of VZnO in colorectal cancer treatment. Furthermore, as an H2S-responsible nanosystem, VZnO appears to have no therapeutic effect on other non H2S rich cancers, such as the 4T1 breast cancer model.We anticipate that the H2S-depletion-induced ferroptosis strategy using zinc oxide-based nanomaterials would provide insights in designing nanomedicines for colorectal cancer-target theranostics and may offer clinical promise.